Clinical validity of a DPYD‐based pharmacogenetic test to predict severe toxicity to fluoropyrimidines. Issue 12 (14th July 2015) - Toffoli, Giuseppe; Giodini, Luciana; Buonadonna, Angela; Berretta, Massimiliano; De Paoli, Antonino; Scalone, Simona; Miolo, Gianmaria; Mini, Enrico; Nobili, Stefania; Lonardi, Sara; Pella, Nicoletta; Lo Re, Giovanni; et al.
<x xml:space="preserve">Abstract</x> Pre‐therapeutic DPYD pharmacogenetic test to prevent fluoropyrimidines (FL)‐related toxicities is not yet common practice in medical oncology. We aimed at investigating the clinical validity of DPYD genetic analysis in a large series of oncological patients. Six hundred three cancer patients, treated with FL, have been retrospectively tested for eight DPYD polymorphisms (DPYD‐rs3918290, DPYD‐rs55886062, DPYD‐rs67376798, DPYD‐rs2297595, DPYD‐rs1801160, DPYD‐rs1801158, DPYD‐rs1801159, DPYD‐rs17376848) for association with Grade ≥3 toxicity, developed within the first three cycles of therapy. DPYD‐rs3918290 and DPYD‐rs67376798 were associated to Grade ≥3 toxicity after bootstrap validation and Bonferroni correction (p = 0.003, p = 0.048). DPYD‐rs55886062 was not significant likely due to its low allelic frequency, nonetheless one out of two heterozygous patients (compound heterozygous with DPYD‐rs3918290) died from toxicity after one cycle. Test specificity for the analysis of DPYD‐rs3918290, DPYD‐rs55886062 and DPYD‐rs67376798 was assessed to 99%. Among the seven patients carrying one variant DPYD‐rs3918290, DPYD‐rs55886062 or DPYD‐rs67376798 allele, not developing Grade ≥3 toxicity, 57% needed a FL dose or schedule modification for moderate chronic toxicity. No other DPYD polymorphism was associated with Grade ≥3 toxicity. Our data demonstrate the clinical validity and specificity of the DPYD‐rs3918290, DPYD‐rs55886062, DPYD‐rs67376798 genotyping test to prevent FL‐related Grade ≥3 toxicity and to preserve treatment compliance, and support its introduction in the clinical practice.